Global health risks mortality and burden of disease attributable to selected major risks - World Health Organization (Geneva, Switzerland World Health Organization, 2009)
This publication is a comprehensive assessment of leading risks to global health. It provides detailed global and regional estimates of premature mortality, disability and loss of health attributable to 24 global risk factors.--Publisher's description.
Introduction. Purpose of this report -- Understanding the nature of health risks -- The risk of transition -- Measuring impact of risk -- Risk factors in the update for 2004 -- Regional estimates for 2004 -- Results. Global patterns of health risk -- Childhood and maternal undernutrition -- Other diet-related risk factors and physical inactivity -- Sexual and reproductive health -- Addictive substances -- Environmental risks -- Occupational and other risks -- Joint effects of risk factors. Joint contribution of risk factors to specific diseases -- Potential health gains from reducing multiple risk factors -- Conclusions.
Also available online.
Keywords: Diseases -- Risk factors; World health; Epidemiology; Mortality